(untitled) (The Review of Diabetic Studies, 2025)
Background: Worldwide, lung cancer continues to be a significant cause of cancer- related deaths; delayed diagnosis greatly aggravates subpar outcomes. Although data favors low-dose CT screening for high-risk groups, the use of lung cancer screening initiatives in Saudi Arabia is not well recorded. The goal of this research was to evaluate the lung cancer screening frequency, patient features, comorbidities, staging at diagnosis, and therapeutic outcomes at the National Guard Health Affairs (NGHA), Riyadh, Saudi Arabia. Methodology: A retrospective cross-sectional study was conducted including all patients diagnosed with lung cancer at NGHA Riyadh from January 2020 to December 2023. Using a structured data extraction form encompassing demographics, smoking history, comorbidities, screening status, cancer staging, histology, therapy, and outcomes. Data were gathered from an electronic medical records review. Statistical analyses descriptive and comparative, including chi-square tests and logistic regression, were carried out with SPSS. Results: The study covered 164 patients, predominantly male (72.6%) and Saudi citizens (94.4%), with an average age of 65.9 years. Almost half (43.3%) were never smokers. Hypertension (40.8%) and diabetes mellitus (43.9%) were among the most prevalent comorbidities. Only 15.9% of those patients were examined for lung cancer, with low-dose CT accounting for 45% of the examinations. The majority of patients, 57.9%, were diagnosed with advanced-stage disease (stage 4). Adenocarcinoma was the most prevalent histological kind (50%). The primary treatment modality was chemotherapy (46.3%). Screening was not significantly linked with age, staging, or survival outcomes. High rates of disease progression (48.2%) and steady disease (40.9%) were noted. Conclusion: Among individuals at NGHA Riyadh, the results show significant underuse of lung cancer screening and a heavy burden of advanced-stage diagnoses. Enhanced screening programs—particularly low-dose CT targeted at high-risk groups—are necessary to allow earlier detection and so improve clinical outcomes. Improving lung cancer screening awareness and healthcare infrastructure in Saudi Arabia could favorably affect mortality rates.